Architecture interruptus : Wexner Center for the Arts. (Ohio : Wexner Center for the Arts, 2007)
This catalogue, like the exhibition it accompanies, focuses on one single structure designed by influential 20th-century architect Le Corbusier: the Church of Saint-Pierre in the small town of Firminy, France. The project was commissioned in the 1960s and designed by Le Corbusier with a young associate, José Oubrerie. Oubrerie, a professor at The Ohio State University's Knowlton School of Architecture, is now bringing the project to fruition after years of delays and interruptions. The catalogue and exhibition will focus much-deserved attention on this posthumously completed "modern/contemporary" cathedral, which is now once again at the forefront of architectural thought. The publication features documentation of the building during both its early and later phases, including hand-inked drawings from the 1960s, as well as more recent computer-generated printouts. New photographs will spotlight the completed project, contrasting with early photographs of the half-built hulk that occupied this prominent location in Firminy for many years.
Keywords: Le Corbusier, -- 1887-1965.; Oubrerie, Jose